Mutagenicity of paepalantine dimer and glycoside derivatives from Paepalanthus bromelioides - Varanda, Eliana Aparecida [UNESP]; Devienne, K. F.; Raddi, MSG; Furuya, E. M.; Vilegas, Wagner [UNESP] (Elsevier B.V., 2004)
The first isocoumarin isolated from the methylene chloride extract of Paepalanthus bromelioides, named paepalantine (isocoumarin 1), was found to have antimicrobial activity; but, it is mutagenic clastogenic and cytotoxic. Two other isocoumarins, paepalantine-9-O-beta-D-glucopyranoside (isocoumarin 2) and paepalantine-9-O-beta-D-allopyranosyl(1-->6) glucopyranoside (isocoumarin 3) were isolated from the ethanolic extract. A fourth new isocoumarin, also isolated from the methylene chloride extract of the capitula of P. bromelioides, was characterized as an 8-8' dimer of paepalantine and denominated isocoumarin 4. The abilities of isocoumarins 2, 3 and 4 to induce mutations in Salmonella typhimurium strains TA97a, TA98, TA100 and TA102 were investigated. Mutagenic activity was observed in strain TA97a treated with isocoumarin 2 in the presence of S9 mixture. The substitution of H at position 9 by glucose or glucose-allose caused reductions in the mutagenic activities of paepalantine, indicating this to be an important site for these properties. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: isocoumarins; mutagenicity; Salmonella typhimurium